MODIS 3 km and 10 km aerosol optical depth for China: Evaluation and comparison. (March 2017) - He, Qingqing; Zhang, Ming; Huang, Bo; Tong, Xuelian
Abstract: The recently released Moderate Resolution Imaging Spectrometer (MODIS) Collection 6 introduced a fine scale aerosol optical depth (AOD) distribution, the 3 km product, which is expected to perform well in analyzing aerosols and identifying local air pollution, especially in the severely polluted atmosphere of China. However, few detailed evaluations of regional variations have been conducted. In this paper, we evaluate MODIS 3 km and 10 km AOD products for China against ground-based measurements and compare their performance with respect to spatial and temporal variations. The ground validations indicate that the two products are generally correlated well to ground-based observations. Spatially, the 3 km product slightly outperform the 10 km product in well-developed areas of southern China. Temporally, both products perform worse during spring and summer. Atmospheric clouds and underlying surface are two key factors that influence the accuracy and number of retrievals for both products. The comparison analysis reveals the newly introduced AOD product clearly shows good relationships with the coarse resolution retrievals in spatial and temporal variation but significant differences regarding details. The 3 km AOD product provides better aerosol gradients, more retrievals in bare areas of western China and some spikes of diurnal variation in cloudy days. Seasonal comparisons show the 3 km AOD product is higher than the 10 km product in all seasons, especially during spring and summer. Although the 3 km product for China generally performs slightly worse than the 10 km product, the added information of the MODIS 3 km AOD product shows potential for studying local aerosol characterization, and may facilitate studies of air pollution. Highlights: We evaluate and compare MODIS 3 km and 10 km AOD product in China spatiotemporally. The two AOD products are generally correlated well with ground-based observations. 3 km product shows better AOD gradients but less sampling frequency than 10 km AOD. Large difference between the two products in China is exhibited in spring and summer. Clouds and underlying surface obviously affect the two aerosol products.